2008
DOI: 10.1002/masy.200850702
|View full text |Cite
|
Sign up to set email alerts
|

Microphase Separation of Bulk and Ultrathin Films of Polyurethane Elastomers

Abstract: Surmmary: Polyurethane elastomers (PUEs) were synthesized with poly(oxytetramethylene) glycol (PTMG), 4,4 0 -diphenylmethane diisocyanate (MDI) and 1,4-butanediol (BD)/1,1,1-trimethylol propane (TMP) by a prepolymer method. The degree of microphase separation of bulk and ultrathin films for these PUEs was confirmed by Fourier transform infrared (FT-IR) spectroscopy, differential scanning calorimetry (DSC) and atomic force microscopy (AFM). In the bulk films, FT-IR and DSC measurements revealed that the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…The sizes of the hard and soft domains in the x-direction were based on X-ray diffraction data, which indicates a typical hard domain thickness of four MDI/BDO repeat units [20][21][22][23][24][25] , and compositional information, which dictates the volume fractions of hard and soft domains (or their thicknesses). The mass fraction of hard domain in the TPU of this study was roughly 55 ± 2%, for which experimental characterization has been reported previously.…”
Section: System and Methodsmentioning
confidence: 99%
“…The sizes of the hard and soft domains in the x-direction were based on X-ray diffraction data, which indicates a typical hard domain thickness of four MDI/BDO repeat units [20][21][22][23][24][25] , and compositional information, which dictates the volume fractions of hard and soft domains (or their thicknesses). The mass fraction of hard domain in the TPU of this study was roughly 55 ± 2%, for which experimental characterization has been reported previously.…”
Section: System and Methodsmentioning
confidence: 99%
“…568 Often chemical cross-links are introduced via addition of polyol or polyamine. 565 , 566 The commercially available Hydromed hydrogels are linear polymers that have excellent solubility in a wide range of organic solvents. However, their high water uptake, insolubility in aqueous solution and good mechanical stability indicate that microphase separation and physical cross-linking occur, which is typical for polyurethanes.…”
Section: Polymeric Hosts and Supportsmentioning
confidence: 99%
“…This is due to a combination of hydrophobic interactions (aggregation of hydrophobic domains in order to minimize the surface area contacting with bulk water) 569 and hydrogen bonding. 565 …”
Section: Polymeric Hosts and Supportsmentioning
confidence: 99%
“…Thermoplastic polyurethane are composed of soft segments and hard segments arranged alternately and microphase separation is the most prominent characteristic of polyurethane. [1][2][3][4][5] The excellent physical and chemical properties of PU are highly dependent on microphase separation which are generally attribute to chemical incompatibility between the hard and soft segments, in which hard segments tends to form a hard microregion by self-aggregation. [6][7][8][9][10][11] However, microphase separation is usually incomplete and some hard segments may be scattered or embedded into soft segments to form an interface region.…”
Section: Introduction *mentioning
confidence: 99%